Analisis Kecepatan Maju Traktor dan Putaran Pisau Pemotong Pada Pengeprasan Tebu Ratoon - Syafriandi Syafriandi (Department of Agricultural Engineering, Syiah Kuala University, 2012)
Analysis on Forward Speed of Tractor and The Spin of Cutter Knife on Ratoon Sugarcane Stubble ShaverABSTRACT. Cultivating ratoon sugarcane by using a stubble shaver conducted on sugarcane cultivation could save the cost of production. A good cultivation could be done by cutting the rest of the plant to the ground. The tool that commonly used was a hoe and a stubble shaver. Revitalization program that included the production of mechanical tools, in addition to providing lucrative benefits in the production business, on the other hand also had weaknesses in some aspects. To improve the quality and efficiency of the tool functions required the development and improvement tools. For example, the development and improvement efforts on tools sugarcane stubble shaver. Therefore, it still needed to conduct research on sugarcane stubble shaver machines to improve productivity especially in the cultivation of ratoon sugarcane stubble by improving the quality of results that would not break the ratoon sugarcane. The purpose of this study was to analyze the forward speed of the tractor and the blade rotation speed of ratoon sugarcane.